2004
DOI: 10.1017/s0033291704002557
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and neurocognitive responses to sad facial affect are attenuated in patients with mania

Abstract: Patients with mania showed a specific, mood-congruent, negative bias in sad facial affect recognition, which was associated with an abnormal profile of brain activation in paralimbic regions implicated in affect recognition and mood disorders. Functional imaging of facial emotion recognition may be a useful probe of cortical and subcortical abnormalities in mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
119
2
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(137 citation statements)
references
References 25 publications
13
119
2
3
Order By: Relevance
“…We did not detect elevations in amygdala response in these BD participants to faces depicting negative emotional expressions, as have been noted in previous studies of BD participants (Yurgelun-Todd et al 2000, Lawrence et al 2004. Possible explanations include limitations in the power to detect differences owing to the small sample size, as well as the inclusion of BD participants with elevated mood symptoms, as attenuated amygdala response to faces depicting negative affect have been reported in association with manic symptoms in BD (Lennox et al 2004).…”
Section: Discussionsupporting
confidence: 57%
“…We did not detect elevations in amygdala response in these BD participants to faces depicting negative emotional expressions, as have been noted in previous studies of BD participants (Yurgelun-Todd et al 2000, Lawrence et al 2004. Possible explanations include limitations in the power to detect differences owing to the small sample size, as well as the inclusion of BD participants with elevated mood symptoms, as attenuated amygdala response to faces depicting negative affect have been reported in association with manic symptoms in BD (Lennox et al 2004).…”
Section: Discussionsupporting
confidence: 57%
“…11,12 Also, recent imaging studies have suggested the involvement of the subgenual cingulate cortex, together with prefrontal areas, in the neurobiology of bipolar disorder 31 and manic and hypomanic states. 32 These findings may suggest that the abnormal functioning of the brain regions implicated herein could be related to the expression of irritability not only in the context of depression, but also in that of manic and/or mixed states. 14 The pattern of increased activity in the BA 9 portion of the left dorsomedial prefrontal cortex, which was present during the presentation of irritability scripts relative to the neutral emotional state, is unlikely to be specifically related to the emergence of irritability emotions.…”
Section: Discussionmentioning
confidence: 78%
“…Structural MRI (sMRI) studies in bipolar adults find either increased or unchanged amygdala volume relative to controls (8)(9)(10), whereas functional MRI (fMRI) studies find that adults with BD, relative to controls, have either amygdala hyperactivation (11,37) or hypoactivation (12) in response to facial stimuli. In contrast to adult data, sMRI studies in bipolar children consistently document decreased amygdala volume in patients compared with controls (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%